Significant up-regulation of 1-ACBP, B-ACBP and PBR genes in immune cells within the oesophageal malignant tissue and a possible link in carcinogenic angiogenesis - Dlamini, Zodwa; Mbele, Mzwandile; McCabe, Michelle; Rees, Jasper; Naicker, Saraladevi; Mbita, Zukile (My University, 2017)
Summary.Oesophageal cancer ranks as the sixth most common malignancy in the world, and recent evidence has shown that its incidence is increasing. ACBPs (AcylcoA binding proteins) act as intracellular carrier-proteins for medium to long chain acyl-coA, mediating fatty acid transport to the mitochondrion for β-oxidation. ACBPs are also believed to be putative ligands of PBR (peripheral benzodiazepine receptor), and once they bind to this receptor they facilitate mitochondrial membrane permeabilization, presumably favouring apoptosis. The main aim of the study was to establish the expression patterns of 1- Acyl-coA binding proteins (1-ACBP), BAcyl-coA binding proteins (B-ACBP), and peripheral bezodiazepine receptor (PBR) in oesophageal cancer, and to link their roles with the disease. In situ hybridization and quantitative real-time PCR methods were performed to determine localization and the expression levels of the three genes in oesophageal cancer. All three genes products illustrated substantial up-regulation within the malignant tissue sections as compared to normal oesophageal sections. All three transcripts localized specifically to mast cells, plasma cells and lymphocytes in diseased and normal tissue section. In the diseased tissue, B-ACBP and 1-ACBP mRNA localized to endothelial cells of blood vessels in the submucosa. B-ACBP also localized to the nucleus of squamous epithelial cells. PBR localization was found in tumour islands of invasive tissue sections. Quantitative RT-PCR also indicated that the expression levels of PBR were higher as compared to the ACBP genes expression in tumours. These results show that 1-ACBP, B-ACBP and PBR play a role in the pathogenesis of oesophageal tumours and possibly in carcinogenic angiogenesis.
Journal article published in the journal of Histology and Histopathology (2017) 32: 561-570
Keywords: Oesophagus cancer; 1-ACBP (AcylcoA binding proteins); B-ACBP (BAcyl-coA binding proteins); Esophagus -- Cancer